OKTAWIUSZ JUREWICZ (30 IV 1926–28 IV 2016) - Kozłowski, Michał (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The paper contains a presentation of the profile and scholarly achievements of the famous Polish classicist and byzantinologist Professor Oktawiusz Jurewicz (1926–2016). Moreover, a list of his publications is included.